Les Syriens en mer Rouge et en Arabie du Sud aux premiers siècles de notre ère : apports de l’iconographie - Jean-François Breton (Frontière·s)
Two bas-reliefs, decorated with motifs of deployed carriages (attelages déployés in French), dating from the first centuries AD, have recently been discovered in South Arabia. Both reliefs depict a nimbed deity standing on a chariot drawn by wild animals, lions or bulls. This is an Eastern iconography that spread to the Palmyra region and beyond, reaching Iran and Central Asia. These two are completed by a stone relief from Shabwa, the capital of the kingdom of Hadhramawt, depicting an armored divinity, also nimbed. These three bas-reliefs raise unprecedented questions about the presence of Syrian (oriental) gods in South Arabia, frequented by Syrian merchants, and indirectly about the existence of places of worship or sanctuaries that archeology does not have discovered yet.